(3OjhGf GdHQYjs - (3GdHQYj , YHO GdQMje Hf CMeO Hf Ydj GdjeGfj,J (B803 (3g` s
(3ChdgG (B:s
(3hHYO(B: (3agPG OjhGf dWja TQja LGeY deG bGdg GdTjN YHOGdQMje GdHQYj ef GdbUGFO GdfHhjGJ hZjQgG Cef JPcQ Cgfd GdHGf hGdHGf Cef JPcQ LjQGf HLjQGf s
(3BNQgG (B:s
(3GdbGFehf haj GdeVGLY dPI GdUGFehf hddgLjQ JhbO OeJe OhGe GdOjf jG TgH GdgOi hYdjce efj GdSdGe GdSQeO s
(3CcKQ GdOjhGf aj GdeOGFM GdfHhjIs
(3bQf GdfSN (B:s
(3GdbQf GdMGOj YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B4 - (3U (B118s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B1 - (3bSe (B3 - (3U (B41 s
Keywords: (3GdCOHs